PENDAMPINGAN DAN TEMU BISNIS BAGI DIFABELPRENEUR KOTA DENPASAR - Sayu Ketut Sutrisna Dewi; I Gusti Bagus Wiksuana; Ida Bagus Anom Purbawangsa (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
The term "difable" for people with disabilities is nowadays preferred because it is seen as more appropriate. People with disabilities in Denpasar City have the desire to be independent and achieve equality with other communities. The difables are also actively pioneering businesses in the creative industry sector, and they are called "difabelpreneurs." There are three main problems faced by difabelpreneurs, namely low business and management knowledge, limited access to capital, and restricted marketing reach. The Community Service activity in the form of mentoring and business meetings for Difabelpreneurs in Denpasar City aims to improve business and management knowledge and expand access to capital and marketing sources. The results of the activity showed an increase in business and management knowledge, as well as the establishment of capital and marketing cooperation.